Emblica officinalis a protective herbal supplementation to prevent buffalo calf mortality - PRIYADARSHINI, LAKSHMI (Indian Journal of Dairy Science, 2016)
ABSTRACT Emblica officinalis (Amla) is widely used in the Unani and Ayurvedic system of medicine and believed to augment immunological status against diseases. Since the buffalo calves are highly susceptible to infectious diseases, this leads to reduce the economy of dairy industry and good quality germplasm. In the present research investigation a possibility was explored in enhancing weight gain, immune status of buffalo calves and alteration in certain hormonal profile by Emblica officinalis supplementation. A total of 12 buffalo calves were selected and divided into two groups. Treatment group consist of 6 calves which were supplemented with amla at 250 mg/kg of body weight for 28 days and control group consist of unsupplemented 6 calves. 5 ml blood samples were collected aseptically from control and all experimental animals on day 28th and 42nd of the age of calves from the jugular vein for analysis of endocrine (cortisol, triiodotyronine and thyroxin) and immunological parameters. In the present investigation a significant (p<0.05) higher body weight gain was observed in Emblica officinalis treated group (7.33 ± 0.49 kg) as compared to control group (5.5 ± 0.56 kg) buffalo calves. Serum cortisol hormone was significantly (p<0.05) lower in treatment group (22.08 ± 2.20 ng/ml) as compared to control group (40.26 ± 2.92 ng/ml). No significant change was observed in the level of T3 hormone in treatment group (1.70 ± 0.22 ng/ml) as compared to control group (1.25 ± 0.14 ng/ml) whereas, higher level of T4 hormone observed in treatment group (3.30 ± 0.62 ng/ml) as compared to control group (0.83 ± 0.09 ng/ml). A higher level of immunoglobulin was observed in Emblica officinalis treated group (1.98 ± 0.10 g/dl) as compared to control group (1.07 ± 0.08 g/dl). Also, adaptability coefficient showed significant higher in treatment group (84.67 ± 1.71) as compared to control group (75.33 ± 3.02). By altering all these parameters it provides a viable tool for enhancing the survivability of buffalo calves in early stage of life. Keywords: Emblica officinalis, Murrah buffalo calves, Immunology, Cortisol, Thyroid, Adaptability coefficient